Kink mechanism in Cu/Nb nanolaminates explored by in situ pillar compression. (15th September 2022) - Zhang, Yifan; Li, Nan; Schneider, Matthew M.; Nizolek, Thomas J.; Capolungo, Laurent; McCabe, Rodney J.
Abstract: Nano metallic laminates (NMLs) exhibit different failure modes depending on the loading conditions due to their mechanical anisotropies. Kinking is a typical failure mode in many NMLs compressed along a layer-parallel direction. However, a detailed description of the microstructure evolution during kink band (KB) formation and an in-depth understanding of the formation mechanisms are lacking. In this work, the KB process is investigated in Cu/Nb NMLs by in situ micro pillar compression in the scanning electron microscope (SEM) along a layer-parallel direction. Post-mortem S/TEM and transmission Kikuchi diffraction (TKD) analyses show that kink banding leads to significant microstructure changes characterized by an accumulation of geometrically necessary dislocations (GNDs) and of tilt geometrically necessary boundaries (GNBs) near KB boundaries (KBBs). The distinct microstructure evolution implies that KB formation is facilitated by the inhomogeneous microstructures resulting in constrained deformation modes. Specifically, dislocations active on slip planes nearly parallel to the interfaces make a major contribution to kink evolution after the onset of kinking. Once layer-parallel slip systems are activated, preexisting lattice dislocations and dislocations nucleating from interfaces will accumulate as GNDs near KBBs via the stochastic storage of lattice dislocations that have certain Burgers vectors. GNDs can further transform into GNBs via cross-slip and climb driven processes near the KBB. Furthermore, GNBs near KBBs can grow by incorporating more GNDs or by coalescence to accommodate the KB evolution. We further hypothesize that microstructural perturbations and their ensuing stresses can initiate KB formation in Cu/Nb NMLs. Graphical abstract: Image, graphical abstract